Quinacrine-Mediated Inhibition of Nrf2 Reverses Hypoxia-Induced 5-Fluorouracil Resistance in Colorectal Cancer - Kim, Ha Gyeong (Int J Mol Sci, 2019)
5-Fluorouracil (5-FU) is an important chemotherapeutic agent for the systemic treatment of colorectal cancer (CRC), but its effectiveness against CRC is limited by increased 5-FU resistance caused by the hypoxic tumor microenvironment. The purpose of our study was to assess the feasibility of using quinacrine (QC) to increase the efficacy of 5-FU against CRC cells under hypoxic conditions. QC reversed the resistance to 5-FU induced by hypoxia in CRC cell lines, as determined using ATP-Glo cell viability assays and clonogenic survival assays. Treatment of cells with 5-FU under hypoxic conditions had no effect on the expression of nuclear factor (erythroid-derived 2)-like 2 (Nrf2), a regulator of cellular resistance to oxidative stress, whereas treatment with QC alone or in combination with 5-FU reduced Nrf2 expression in all CRC cell lines tested. Overexpression of Nrf2 effectively prevented the increase in the number of DNA double-strand breaks induced by QC alone or in combination with 5-FU. siRNA-mediated c-Jun N-terminal kinase-1 (JNK1) knockdown inhibited the QC-mediated Nrf2 degradation in CRC cells under hypoxic conditions. The treatment of CRC xenografts in mice with the combination of QC and 5-FU was more effective in suppressing tumor growth than QC or 5-FU alone. QC increases the susceptibility of CRC cells to 5-FU under hypoxic conditions by enhancing JNK1-dependent Nrf2 degradation.